A prospective and open-label study for the efficacy and safety of telbivudine in pregnancy for the prevention of perinatal transmission of hepatitis B virus infection - Han, Guo-Rong; Cao, Min-Kai; Zhao, Wei; Jiang, Hong-Xiu; Wang, Cui-Min; Bai, Shu-Fen; Yue, Xin; Wang, Gen-Ju; Tang, Xun; Fang, Zhi-Xun (Journal of hepatology, 2011)
In the Asia–Pacific region, perinatal transmission of the hepatitis B virus (HBV) is the primary cause of chronic hepatitis B infection. Despite the use of HBIG and HBV vaccination, HBV perinatal transmission (PT) occurs in 10–30% of infants born to highly viremic mothers. We evaluated the efficacy and safety of LTD use during late pregnancy in reducing HBV transmission in highly viremic HBeAg+mothers. Two hundred and twenty-nine HBeAg+HBV DNA levels>1.0×107 copies/ml mothers received telbivudine 600mg/day from week 20 to 32 of gestation (n=135) or served as untreated controls (n=94). All infants in both arms received 200IU of HBIg within 12h postpartum and recombinant HBV vaccine of 20μg at 0, 1, and 6months. HBsAg and HBV DNA results of infants at week 28 were used to determine perinatal transmission rate. All telbivudine treated subjects were registered in the Antiretroviral Pregnancy Registry. Telbivudine treatment was associated with a marked reduction in serum HBV DNA and hepatitis B e antigen (HBeAg) levels and normalization of elevated ALT levels before delivery. A striking decline of HBV DNA levels started from treatment onset to week 4, and sustained in a low level since week 12. Forty-four (33%) of the 135 telbivudine-treated mothers and none (0%) of the untreated controls had polymerase chain reaction-undetectable viremia (DNA<500 copies/ml) at delivery. Seven months after delivery, the incidence of perinatal transmission was lower in the infants that completed follow-up born to the telbivudine-treated mothers than to the controls (0% vs. 8%; p=0.002). HBV DNA levels were only detectable in HBsAg+infants. No significant differences in anti-HBs levels were observed during postnatal follow-up. No serious adverse events were noted in the telbivudine-treated mothers or their infants. Telbivudine used during pregnancy in CHB HBeAg+highly viremic mothers can safely reduce perinatal HBV transmission. Telbivudine was well-tolerated with no safety concerns in the telbivudine-treated mothers or their infants on short term follow up. These data support the use of telbivudine in this special population.